Genetic polymorphisms within the human Toll-like receptor 2 subfamily. (23rd November 2007) - Tapping, R.I.; Omueti, K.O.; Johnson, C.M.
Abstract : Infectious disease is a formidable selective force in Nature as is evident from the complexity of immune systems across multicellular species. TLRs (Toll-like receptors) constitute central pattern-recognition molecules of the innate immune system that sense bacterial, viral, fungal, protozoan and helminth organisms and activate responses that provide immediate as well as long-term protection for the host. The present article reviews the function and evolution of vertebrate TLRs with an emphasis on the subfamily of receptors comprising human TLR1, 2, 6 and 10. The idea that TLRs undergo strong purifying selection provides the framework for the discussion of single nucleotide polymorphisms, many of which are associated with the incidence of infectious disease.